Teaching Factory Management in Improving the Quality of Graduates in Accordance with Industry Needs - Galih Nalapraya; H Helmawati, (Journal of Science and Education (JSE), 2025)
This research is based on the high Open Unemployment Rate (TPT) of Vocational High School (SMK) graduates in Indonesia, which reached 8.00% in February 2025, although there has been a decline from the previous year. This phenomenon shows the misalignment between the competencies of vocational school graduates and the needs of the industry. Vocational schools as vocational education institutions are expected to produce graduates who are ready to work, both in terms of hard skills and soft skills, but in reality there are still many graduates who have not met industry standards. Therefore, an effective management approach is needed to improve the relevance and quality of graduates. The purpose of this study is to describe and analyze the management of Teaching Factory (TEFA) in improving the quality of graduates in accordance with the needs of the industry at SMK BPI Bandung. This research uses management theory from G.R. Terry which includes four management functions: planning, organizing, implementing, and evaluating. The research method used is a single case study to explore in depth the application of TEFA at SMK BPI Bandung. The results of the study show that the implementation of the four management functions of Terry in a holistic and synergistic manner has proven to be effective in improving the competence of graduates. Planning based on industry needs, collaborative organization, implementation through real job orders, and continuous evaluation have succeeded in creating graduates who are relevant to the demands of the world of work. The obstacles that arise are overcome through the addition of facilities, the improvement of teacher competence, and the strengthening of industry partnerships. The conclusion of this study is that the management of the Teaching Factory at SMK BPI Bandung has been effective and has succeeded in improving the quality of graduates. Strategic synergy with industry is the key to success, and emphasizes that a systematic and adaptive management approach is a fundamental prerequisite for the success of the TEFA program in the vocational education system